The Islamization of Jhon Locke’s Justice Theory: Integration of Islamic Concepts and Jhon Locke’s Theory of Justice - Mohammad Latief; Muhammad Fajar Pramono; Shanaz Nurzaini Bey (Hikmatuna : Journal for Integrative Islamic Studies, 2023)
The Study world is faced with inter-community conflict, which creates disparities in social life. From this, John Locke tried to bring up the theory and concept of justice to achieve a prosperous society, but John Locke's theory and concept of justice ended in social capitalism and the behavior of prejudicial others that comes with critics from the Westerns. So, the purpose of writing this paper is to criticize John Locke's theories and concepts of justice with several theories of justice from other scientists, reveal the positive and negative sides of the whole, then only take the positive side. The writing of this paper uses the analytical-descriptive method to describe the theory of justice by John Locke and several other scientists, then analyze it to reach criticism and the positive and negative sides. So then by writing this paper will contribute to the integration of John Locke's concept of justice with including Islamic values. The result of integrating the concept of justice is that John Locke plays a role in expressing that there is a lack of wishful thinking about John Locke's concept of justice and the Islamic concept that can gain prohibition demonstrating that the Islamic law concept can support any tone without compromising any side.